Longitudinal study on the genetic diversity of extended-spectrum cephalosporin resistant Escherichia coli in Dutch veal calves - Bello Gonzalez, T. d. J.; Marcato, F.; Veldman, K. T.; Wolthuis-Fillerup, M.; Harders, F.; van Reenen, K.; Brouwer, M. S. M. (Frontiers in Microbiology, 2025)
The present study aimed to evaluate the genetic diversity of Extended Spectrum Cephalosporin resistant (ESC-R) E. coli isolates obtained from Dutch veal calves during a longitudinal study, to better understand the genetic background behind the persistent ESC-R E. coli colonization in the dairy and veal sectors. Rectal swabs were collected from 683 calves located in 13 Dutch dairy farms 1 day prior to their transportation to 8 veal farms. At the veal farms, rectal swabs were collected at 5 different time points after arrival. A total of 1,202 ESC-R E. coli isolates were obtained through selective isolation. Nine out of 13 dairy farms were positive for ESC-R E. coli (n = 175 isolates), arbitrarily divided in a high prevalence (>50%, n = 7) or low prevalence farms (<5%, n = 2) In three veal farms, a relatively high frequency of ESC-R E. coli was observed (range = 38–84%) while in the remaining five farms, a lower frequency was observed (range = 5–24%). At veal farms, the highest average ESC-R E. coli frequency was detected in week two (57.3%). ESBL/AmpC encoding genes were identified by RT-PCR and amplicon sequencing. ESBL genes (blaCTX-M-1 groups, blaCTX-M-9 group) and specific point mutations in the promotor region of the chromosomal blaampC gene were identified both at dairy farms and veal farms. A total of 364 ESC-R E. coli isolates were further characterized by WGS to determine the genetic relationship using core genome Multi Locus Sequencing Typing (cgMLST). The ESBL-genes blaCTX-M-1 and blaCTX-M-15 were predominant, the majority in combination with a non-ESBL blaTEM-1 gene. In addition, genes encoding resistance against quinolones, aminoglycosides, phenicols, tetracyclines, sulfonamides, and trimethoprim were identified in these isolates. Finally, phylogenetic analysis showed a diverse pool of E. coli strains carrying the blaCTX-M-1 gene, while two genetically closely related sequence types (STs) were identified in E. coli strains carrying the blaCTX-M-15, being ST 4981 and ST 2325, the most predominant STs identified. Our results revealed a population of ESC-R E. coli which are genetically similar within veal farms and provides evidence of direct transmission and dissemination of ESC-R E. coli between the animals during the rearing process.